TEORI DASAR SIMULASI PROSES PEMBAKARAN LIMBAH VINASSE DARI INDUSTRI ALKOHOL BERBASIS CFD (Universitas Negeri Semarang, 2013)
In the midst of restrictions issue on the use of fossil fuels, the world began to move towards the use of renewable fuels. One such fuel is bio-ethanol. Production of bio-ethanol itself leaves vinasse wastetreatment problems with large discharge. There have been many ways to treat vinasse one of which is the burning of concentrated vinasse. Combustion process is a complex process in terms physical and chemical. Complex phenomenon will be difficult to be analyzed simultaneously and comprehensively when using conventional techniques. Simulation of combustion process based on CFD can be one such solution. In the case of vinasse as fuel and air as oxydizer the selected combustion model is a non-premixed combustion models with probability density function.